Water security under climate change - abstract - Singh, Vijay P., author; Colorado State University, publisher (Colorado State University. Libraries, 2013)
Abstract of award lecture "Water security under climate change" given on March 26, 2013 by Vijay P. Singh, winner of the 2013 Hydrology Days Award.
Hydrology days 2013
AGU hydrology days 2013
2013 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2013.
Keywords: Hydrology -- Congresses; Award winners